Gonadotrophin therapy in Kallmann syndrome caused by heterozygous mutations of the gene for fibroblast growth factor receptor 1: report of three families:Case report - Sato, Naoko; Hasegawa, Tomonobu; Hori, Naoaki; Fukami, Maki; Yoshimura, Yasunori; Ogata, Tsutomu (Human reproduction (Oxford), 2005)
Gonadotrophin therapy (GT) is frequently used to induce fertility in Kallmann syndrome (KS). We studied the effects and the consequences of GT in autosomal dominant KS caused by heterozygous FGFR1 mutations. Three Japanese families were examined. In family A, an adult male received GT and had two sons. In family B, an adult female received GT and gave birth to dizygotic male and female twins. In family C, an adult female received GT and produced a son and a daughter. Direct sequencing was performed for FGFR1, and clinical assessment was carried out for KS features. The father and the elder son of family A had P745S mutation, the mother and the female twin of family B had G687R mutation, and the mother and the two children of family C had S107X mutation. KS phenotype was detected for the mutation-positive subjects, except for the elder son of family A who had apparently normal phenotype. GT in FGFR1 mutations is effective in acquiring fertility but has a risk of transmitting the mutation and the disease phenotype to the next generation.